Quality Assurance in Pesantren: Modernization, Adaptability, and Integration into Indonesia’s Education System - Zahra Khusnul Lathifah; R. Siti Pupu Fauziah; Radif Khotamir Rusli; Martin Roestamy; Abraham Yazdi Martin; Syukri Indra; Uman Suherman (Jurnal Pendidikan Islam, 2025)
This research highlights the critical role of quality assurance in Islamic boarding schools, which are integral to the development of Islamic Education in Indonesia. The primary objective of this study is to employ bibliometric analysis to assess the research achievements, identify national and international networks, and map emerging trends in quality assurance for Islamic boarding schools using Google Scholar data from 2017 to 2021. The study utilized bibliometric methods, including publication, authorship, and citation analysis, and employed VOSviewer software to map the bibliometric data. The analysis revealed 996 scientific publications related to quality assurance and Islamic Education, yielding 6,139 citations and 125 interconnection thresholds. Key terms with strong interconnections include “school,” “private school,” “education,” “Indonesia,” and “student.” Notably, no prior studies have applied bibliometric mapping to explore quality assurance in Islamic boarding schools, highlighting this study’s novel contribution. The findings emphasize the importance of pesantren institutions in preserving local wisdom and their role in nation-building. This research has significant implications for Islamic Education, particularly in urging policymakers to strengthen government policies that enhance the quality and relevance of Education in Islamic boarding schools, ensuring their continued contribution to national development.